Autonomic dysreflexia – neurovegetative syndrome - AH, Azhar; AR, Mosassadeq; MD, Mohd Ashraf; Kamarulzaman, Mohd Nazli; Rahman, Mohd Nor Gohar; Z, Mahamood (Universiti Sains Malaysia, 2008)
Autonomic dysreflexia is an exaggerated uninhibited sympathetic response to afferent stimulation following spinal cord injury above T6 level.